Research Trends of Virtual Laboratory in Science Learning to Improve Affective Domain: a Systematic Literature Review - Lailiyah, Nurul Wahyuni; Widarti*, Hayuni Retno; Munzil, Munzil; Surif, Johari (Jurnal Pendidikan Sains Indonesia, 2024)
A virtual laboratory is a simulated environment that enables users to conduct various experiments anytime and anywhere without the need for a physical laboratory. Its main goal is to identify trends (such as publication year, education level, publication journal, keywords used, and academic disciplines) and map the platforms and affective domains related to virtual laboratories in science education. This systematic review utilizes 41 articles found in the scopus database from 2013 to 2023 using pre-determined criteria. The method applied is a systematic literature review following PRISMA guidelines. The results show that publication trends have fluctuated over time, with a significant increase in the last four years. Most studies were conducted at the higher education level, with the journal of chemical education being the most dominant publication outlet. Chemistry emerged as the most frequently explored discipline, and "virtual laboratory" appeared as a commonly used keyword. Various virtual laboratory platforms were employed in these studies, and most of the reported affective domains related to positive attitudes towards the learning process